Laplacian filtering effect on digital image tuning via the decomposed eigen-filter. (September 2019) - Du, Zhenlong; Li, Xiaoli
Abstract: The Laplacian filter is widely used for acquiring the image edge in the fields of image processing and computer vision due to its excellent edge acquisition capability. However, little deep research on Laplacian filtering exists besides the conventional hierarchical handling technique. In this paper, the essence of Laplacian filter and filtering is investigated, the eigen-filters are extracted from the Laplacian filtering influence scale space, and the spectrum relevance eigen-filters are shown to represent different spectral filtering. Based on the extracted eigen-filters, a subtle filtering effect can be achieved by tuning a group of eigen-filter scalars. The experiments on the subtle filtering effect adjustment demonstrate that the given approach could extract the characteristic eigen-filter, which plays the essential role in Laplacian filtering.